The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1287/opre.1100.0874
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Layout on Productivity: An Analysis from Robotic-Cell Manufacturing

Abstract: Although the impact of layout on the productivity of manufacturing systems is well recognized, a quantification of this impact is an issue that is often ignored or crudely approximated in practice. When evaluating competing layouts for a manufacturing system, the trade-off between their relative benefits and their relative costs underlines the need for a reasonably accurate comparison of the productivity offered by these potential layouts. In this paper, we argue for this approach by comparing the productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…1(a) travels from the output buffer O to machine M 1 by moving counterclockwise (passing I, time 2δ) because clockwise travel (traversing machines M 5 , M 4 , M 3 , and M 2 , time 5δ) would require more time. This flexibility in robot movements can significantly improve the productivity of a cell; however, the sequencing of operations becomes more challenging, even for single-gripper cells (Brumson, 2001;Rajapakshe et al, 2011). Furthermore, schedules that are optimal in linear cells are not necessarily optimal in circular cells (Geismar, Sethi, Sidney, and Sriskandarajah, 2005), so different techniques are required to find efficient robot sequences.…”
Section: Introductionmentioning
confidence: 99%
“…1(a) travels from the output buffer O to machine M 1 by moving counterclockwise (passing I, time 2δ) because clockwise travel (traversing machines M 5 , M 4 , M 3 , and M 2 , time 5δ) would require more time. This flexibility in robot movements can significantly improve the productivity of a cell; however, the sequencing of operations becomes more challenging, even for single-gripper cells (Brumson, 2001;Rajapakshe et al, 2011). Furthermore, schedules that are optimal in linear cells are not necessarily optimal in circular cells (Geismar, Sethi, Sidney, and Sriskandarajah, 2005), so different techniques are required to find efficient robot sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical design often seems to buy a lottery on the final cell productivity via its respective cost-benefit analysis. 9 Over the years, many previous studies trying to give a problem-solving answer have taken some steps forward in this area. Mata and Tubaileh discuss the workstation layout problem in manufacturing cell served by a single robot.…”
Section: Patterned Layout Optimizationmentioning
confidence: 99%
“…In contrast, Akturk et al (2005) studied flexible cells using a linear cell layout. Rajapakshe et al (2011) showed that the problem RF 1;1 m• |free,A,cyclic-1|C t is NP-hard. Our current article analyzes circular cells with dual-arm robots by examining all possible sequences, calculating their respective throughputs under this travel time metric, and determining the specific circumstances under which each is optimal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is common in the literature. Examples include Sethi et al (1992), Lei and Wang (1994), Crama and Van de Klundert (1997), Hall et al (1997), Levner et al (1997), Venkatesh et al (1997), Agnetis (2000), Herrmann et al (2000), Brauner and Finke (2001), Che et al (2003), , Akturk et al (2005), Kumar et al (2005), Dawande et al (2010), and Rajapakshe et al (2011). Thus, any part in the cell is always either on one of the machines or being handled by one of the two robot arms.…”
Section: Introductionmentioning
confidence: 99%